Odpowiedź :
a) (x-1)² = x²
x² -2x + 1 - x² = 0
-2x=-1 /:(-2)
x=o,5
b) 3x+(6x+1)²=4(5+9x²)-4
3x + 36x² + 12x + 1 = 20 + 36x² - 4
15x= 15/ :15
x=1
c) (-3x+6)²-2+3x(3x-11)=31
9x² - 36x + 36 -2 + 9x² - 33x = 31
-69x = 31 - 34
-69x = -3 /:(-69)
Nie wiem, czy dobrze zrobiłam ten przykład ;/
d)( -6+2)²=-3(4-12x²)
36 - 24 + 4 = - 12 + 36x²
- 36x² = -12 - 16
- 36x² = - 28 /:(-36)
x² = 28/36 /:√
x=√28/36
Zad. 2
Nie mam siły dalej robić;p
x² -2x + 1 - x² = 0
-2x=-1 /:(-2)
x=o,5
b) 3x+(6x+1)²=4(5+9x²)-4
3x + 36x² + 12x + 1 = 20 + 36x² - 4
15x= 15/ :15
x=1
c) (-3x+6)²-2+3x(3x-11)=31
9x² - 36x + 36 -2 + 9x² - 33x = 31
-69x = 31 - 34
-69x = -3 /:(-69)
Nie wiem, czy dobrze zrobiłam ten przykład ;/
d)( -6+2)²=-3(4-12x²)
36 - 24 + 4 = - 12 + 36x²
- 36x² = -12 - 16
- 36x² = - 28 /:(-36)
x² = 28/36 /:√
x=√28/36
Zad. 2
Nie mam siły dalej robić;p
a)(x-1)²=x²
x²-2x+1-x²=0
-2x=-1
x=1/2
b) 3x+(36x²+12x+1)=20+36x²-4
3x+36x²+12x+1-20-36x²+4=0
15x-15=0
15x=15
x=1
c)(9x²-36x+36)-2+9x²-33x-31=0
9x²-36x+36-2+9x²-33x-31=0
18x²-69x+3=0
delta=b²-4ac=4761-216=4545
x₁=(69-√4545)/36
x₂=(69+√4545)/36
d)(36-24+4)=-12+36x²
16+12-36x²=0
-36x²+28=0
delta=0+4032=4032
x₁=(-√4032)/-72=√4032/72
x₂=√4032/-72
zad 6
a)(9x²+12x+4)-9x²-15=0
12x-11=0
12x=11
x=11/12
b)9x²-12x=9x²-12x+4
9x²-12x-9x²+12x-4=0
-4=0
zero
c)1/2x-4+x=0,25x²-2x
-0,25x²+3,5x-4=0
delta=12,25-4=8,25
x₁=[(-3,5)-√8,25]/-0,5
x₂=[(-3,5)+√8,25]/-0,5
d)0,09y-3,6y=4-1,2y+0,09y²
-3,51y-4+1,2y-0,09y²=0
-0,09y²-2,31y-4=0
delta=5,34-1,44=3,9
x₁=(2,31-√3,9)/-0,18
x₂=(2,31+√3,9)/-0,18
x²-2x+1-x²=0
-2x=-1
x=1/2
b) 3x+(36x²+12x+1)=20+36x²-4
3x+36x²+12x+1-20-36x²+4=0
15x-15=0
15x=15
x=1
c)(9x²-36x+36)-2+9x²-33x-31=0
9x²-36x+36-2+9x²-33x-31=0
18x²-69x+3=0
delta=b²-4ac=4761-216=4545
x₁=(69-√4545)/36
x₂=(69+√4545)/36
d)(36-24+4)=-12+36x²
16+12-36x²=0
-36x²+28=0
delta=0+4032=4032
x₁=(-√4032)/-72=√4032/72
x₂=√4032/-72
zad 6
a)(9x²+12x+4)-9x²-15=0
12x-11=0
12x=11
x=11/12
b)9x²-12x=9x²-12x+4
9x²-12x-9x²+12x-4=0
-4=0
zero
c)1/2x-4+x=0,25x²-2x
-0,25x²+3,5x-4=0
delta=12,25-4=8,25
x₁=[(-3,5)-√8,25]/-0,5
x₂=[(-3,5)+√8,25]/-0,5
d)0,09y-3,6y=4-1,2y+0,09y²
-3,51y-4+1,2y-0,09y²=0
-0,09y²-2,31y-4=0
delta=5,34-1,44=3,9
x₁=(2,31-√3,9)/-0,18
x₂=(2,31+√3,9)/-0,18